2018
DOI: 10.5152/tud.2018.28938
|View full text |Cite
|
Sign up to set email alerts
|

Can multiphase CT scan distinguish between papillary renal cell carcinoma type 1 and type 2?

Abstract: Objective: To investigate the utility of multiphase computed tomography (CT) and percutaneous renal mass biopsy (PRMB) in differentiating between papillary renal cell carcinoma (pRCC)-Type 1 and -Type 2, as emerging data have suggested differential enhancement patterns in different renal tumor histologies. Material and methods:Retrospective analysis of 51 patients (23 pRCC-Type 1/28 pRCC-Type 2) who underwent multiphase CT followed by surgery from July 2011 to April 2016 was performed. Data were analyzed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Most papers [20][21][22][23][24][25][26][27][28][29] that have analyzed the association between attenuation values on MDCT and histological types have shown that the magnitude of enhancement at MDCT can help differentiate ccRCC from pRCC, chrRCC, and oncocytoma. Using measurements of quantitative MDCT enhancement values, our study showed that, among solid cortical renal tumors, the greatest utility in terms of differentiations was between ccRCC and pRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Most papers [20][21][22][23][24][25][26][27][28][29] that have analyzed the association between attenuation values on MDCT and histological types have shown that the magnitude of enhancement at MDCT can help differentiate ccRCC from pRCC, chrRCC, and oncocytoma. Using measurements of quantitative MDCT enhancement values, our study showed that, among solid cortical renal tumors, the greatest utility in terms of differentiations was between ccRCC and pRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Cognizance incorporates each psychological cycle that can be depicted as another experience. 34 On the off chance that AI technique with cognitive framework required to break down a major information data, the artificial intelligence strategy performs well while resolving action depending on given data, while the cognitive framework gives certain data to the client to select a superior outcome. 35 In setting autonomous, completely deterministic frameworks, for example, chess-playing, each activity in every particular state consistently creates a similar outcome and the outcome just relies upon the present status and the current activity, so they do not have to monitor past states.…”
Section: Methodsmentioning
confidence: 99%
“…We can promote intelligence by thinking, figuring out, summoning, and learning. Cognizance incorporates each psychological cycle that can be depicted as another experience 34 . On the off chance that AI technique with cognitive framework required to break down a major information data, the artificial intelligence strategy performs well while resolving action depending on given data, while the cognitive framework gives certain data to the client to select a superior outcome 35 .…”
Section: Methodsmentioning
confidence: 99%
“…The CT manifestation of cystic renal cell carcinoma has high density resolution. Thus, the characteristics of cystic renal cell carcinoma can be analyzed by imaging, which helps to accurately diagnose cystic renal cell carcinoma (5). However, the CT manifestation of cystic renal cell carcinoma is similar to that of other benign cystic lesion.…”
Section: Introductionmentioning
confidence: 99%